Marketing Strategy of STIE Ciputra Makassar in branding itself as an Entrepreneurship-based Private University in Makassar City - Pangemanan, Aurelia Benita; Angelica Tjandra; Vlady Marcelo Sorensen; Novika Ayu Triany (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
The competition of entrepreneur-based private universities in Makassar City is very competitive. Some universities present entrepreneurship as additional learning on campus, but there are also those who make it a course. This is driven by fierce job competition, where companies want employees to have attractive and superior characteristics. This factor will affect the loyalty of customers. The purpose of this study was to find out what strategy STIE Ciputra used in branding itself as an Entreprenaurship-based private university in the city of Makassar. The research data was obtained by making observations and interviews with the Head of STIE Ciputra Makassar where the author concluded that there are 2 strategies used by STIE Ciputra, namely above the line and also below the line to introduce STIE Ciputra to the wider community besides that the division of roles carried out by the leader is very helpful in managing the branding strategy.